Effect of rolling thin film oven-aged binders and aging methods on the performance of hot mix asphalt - Yousif, Rana Amir (2017)
Age hardening of bitumen has long been perceived as one of the main factors that can significantly affect the durability of bituminous paving materials. When the bitumen is age-hardened, the asphalt mixture will become brittle and its ability to support traffic-induced stresses and strains may significantly reduce. Deterioration of the pavement by readily-induced cracking may follow. In addition, excessive hardening can also weaken the adhesion between the bitumen and aggregate, resulting in loss of materials at the surface layer and generating weakening of the asphalt mixture. Furthermore, the performance of asphalt pavements is found to be very poor in moisture induced situations.